New Development Bank and IMF: Bangladesh's Strategic Choices in Facing Economic Crisis - Ravalino, Destha; Kuswardini, Seftina (Nation State: Journal of International Studies, 2025)
This study explores the underlying reasons behind Bangladesh’s preference for cooperating with the New Development Bank (NDB) over the International Monetary Fund (IMF) in addressing its national economic crisis. Using a qualitative-descriptive approach and the theoretical framework of the Global South and minilateralism, the research examines Bangladesh’s development policy dynamics and its response to economic and political pressures, particularly following the military coup in August 2024. The findings indicate that while IMF provides financial support, its conditionalities such as exchange rate liberalization, subsidy removal, and fiscal reforms have adverse effects on public welfare. In contrast, cooperation with NDB offers policy flexibility, equality among member states, and financing support for sustainable projects without structural intervention. This study highlights that NDB serves as a geopolitical tool that enables developing countries to assert economic sovereignty and advance South–South solidarity in the context of an emerging multipolar global economic order. The study suggests that Bangladesh’s engagement with NDB reflects strategic hedging, diversifying external partnerships to reduce dependency on Western-dominated institutions. This choice strengthens domestic policy autonomy, mitigates social backlash, and enhances bargaining power, while signaling alignment with alternative development financing models increasingly favored by Global South.